Kenneth Lonergan's networked Bildungsromane: Howards End (2017) and Margaret (2011). Issue 12 (1st December 2020) - Rooney, Monique
ABSTRACT: This essay analyses Kenneth Lonergan's television miniseries Howards End (2017, screenwriter Lonergan, director Hettie McDonald) and the film Margaret (2011, director and screenwriter Lonergan) as coming-of-age narratives in which tragic storylines pivot on the actions of young, middle-class women who insert themselves into the lives of other people. Deploying but departing from Marxist materialist analyses of the Bildungsroman, namely Franco Moretti's dialectical reading of the modern novel and Francis Mulhern's argument about the 'condition of culture' novel, my reading of Lonergan's Bildungsromane elucidates the significance of the digitally-networked environment in which these media were produced. While the form of the novel is central to Moretti's reading of the Bildungsroman as dialectic of transformation and convention, my analysis of Lonergan's networked Bildungsromane emphasises the role of both mixed-media and connectivity in how female characters are represented. With reference to Sianne Ngai's aesthetic-categorical reading of the 'interesting' as both a curious feeling and a measured evaluation, I focus on the portrayal of 'interested' young women in Lonergan's contemporary screen texts in order to investigate the limits and possibilities of a feminine drive toward resolution for selves and others.